Changes in Soil Organic Matter Parameters during the Period of 18 Years Under Different Soil Management Practices - Šimanský Vladimír (Agriculture, 2016)
Quantity and quality of soil organic matter (SOM) is very important from view point of sustainable agriculture; therefore, during the years 1994–2011, the influence of different soil management practices on changes in SOM parameters in loamy Haplic Luvisol was evaluated in a field experiment in the locality of Dolná Malanta. The field experiment included two types of soil tillage – (1) conventional tillage (CT) and (2) reduced tillage (RT) – and also two treatments of fertilisation – (1) crop residues together with added NPK (nitrogen, phosphorus and potassium) fertilisers (CR + NPK) and (2) added NPK fertilisers. Contents of humic substances (HS) and fulvic acids (FA) under RT increased by 1.6% and 4.4%, respectively, compared to CT during the years 1994–2011. On the other hand, contents of humic acids (HA), HA-to-FA ratios, colour quotient of HS and colour quotient of HA under CT increased by 2.0%, 2.5%, 1.8% and 2.3%, respectively, compared to RT. In CT and RT, HS declined at an average speed of 0.33% and 0.53% per year, respectively. In CR + NPK treatments and application, only NPK fertiliser caused a decline of HS at an average speed of 0.52% and 0.33 % per year, respectively. In CT, RT and CR + NPK treatments, the linear trends (statistical significant) in decline of FA were observed. All in all, the CT had a slightly better effect on the quality of SOM, whilst the stability of SOM was improved by RT. Applications of mineral fertilisers along with crop residues resulted in better quality but lower stability of SOM.